Tinjauan Historis : Kemajuan Sistem Perbankan Syariah Yang Ada Di Asia Tenggara - Anwar L Nata, Andrian; Riani, Novi; Endra Kusuma, Ryo (Margin: Jurnal Bisnis Islam dan Perbankan Syariah, 2023)
Abstract: Southeast Asia is a region that is the center of the development of the Islamic banking and finance industry in the world. Islamic banking in every country, especially in Southeast Asia, in transactions at Islamic banks must be based on sharia principles. The research used is normative legal research. In normative legal research written law can be studied in various aspects, including theory, comparison, formality in the power of law. Based on the results of the research and discussion above, it is concluded that globally, Islamic banking in Southeast Asia is ranked second in the world in terms of its largest assets. The position of Islamic banking in Southeast Asia is highly regarded throughout the world. The biggest challenge that will be faced by Southeast Asian countries in developing an integrated Islamic financial system is the gap in the quality of Islamic finance development in each of the countries that implement it. And in order to build a strong and integrated sharia-based financial area, cooperation between related parties is needed. And the most important condition for Islamic financial integration is the harmonization of regulations between the countries concerned. Sharia banking is generally still run based on a conventional vision even though it is already operating in accordance with sharia principles or sharia compliance. In addition, BRI sharia operating in Indonesia has the highest performance in the maqâshid al-syarî`ah index, which is also followed by Panin Syariah and Muamalat Indonesia. Thus, Islamic banking in Indonesia is leading in terms of the performance of the maqâshid alsyarî`ah index in Southeast Asia. In contrast, countries with minority Muslim populations such as Thailand and the Philippines and Singapore are relatively low in the performance of the maqâshid al-syarî`ah index. The suggestion in this study is that in order to build a strong and integrated sharia-based financial area, cooperation between related parties is needed. By measuring the performance of shari'ah banking in Southeast Asia, it is hoped that it can evaluate the performance of shari'ah banking in Southeast Asia and show that the performance of shari'ah banking is not only based on material, but also pays attention to its shari'ah values.